2023
DOI: 10.1094/pdis-08-22-1986-re
|View full text |Cite
|
Sign up to set email alerts
|

Resistance toFusarium oxysporumf. sp.luffaeinLuffaGermplasm Despite Hypocotyl Colonization

Abstract: Fusarium wilt of Luffa, caused by Fusarium oxysporum f. sp. luffae (Folu), causes great losses in Luffa plants worldwide. In this study, 45 accessions of Luffa germplasm were used to determine their resistance to Folu isolates (FOLUST, FOLUSC, Fomh16, and Fol114) in two independent trials. In the first trial, only FOLUST was used to preliminarily identify resistant accessions. Nine accessions of L. acutangular and five of L. aegyptiaca were resistant to the FOLUST isolate. In the second trial, the other three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…This finding aligns with previous research indicating significant variations in luffa’s resistance to Fusarium wilt across different countries. For instance, there were no instances of Fusarium wilt-resistant luffa in Cambodia and Uzbekistan [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding aligns with previous research indicating significant variations in luffa’s resistance to Fusarium wilt across different countries. For instance, there were no instances of Fusarium wilt-resistant luffa in Cambodia and Uzbekistan [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, luffa production faces substantial losses due to luffa Fusarium wilt, a severe disease caused by the fungus Fusarium oxysporum (Fo). This resilient fungus can persist in the soil for an extended period, and infected plants display symptoms such as slow growth, yellowing of lower leaf, and browning of vascular bundles, ultimately leading to reduced yield and plant fatalities [ 13 ]. While several control methods are currently available, many of them are unsuitable due to cost, effectiveness, and environmental concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Hilal et al (2000) tested fungi isolated from the roots and seeds of Luffa aegyptiaca Mill and found that M. phaseolina was not pathogenic to this crop. Subsequent studies also highlighted the resistance of this cucurbitaceous plant when inoculated with other root pathogens (Bruton et al, 2000;Kwon et al, 2001;Namisy et al, 2023;Bindal et al, 2023).…”
Section: Introductionmentioning
confidence: 98%
“…Cultivars with resistance are the most effective defense against soil-borne diseases. Fusarium wilt-resistant cultivars have been reported in L. acutangula and L. aegyptiaca ( 16 ). However, the resistance mechanism against Folu in the Luffa species is largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…More research studies have indicated that Fon could penetrate and colonize the roots of the highly resistant watermelon line but failed to enter the vascular system ( 23 ) and did not result in wilt symptoms ( 24 ). A previous study reported that four Folu isolates colonized the hypocotyl of highly resistant Luffa accessions without displaying symptoms ( 16 ). This behavior might be similar to Fon in that Folu colonizes hypocotyl in the resistant Luffa but does not move into the vascular system.…”
Section: Introductionmentioning
confidence: 99%